Optimization Expression and Stability Test of Recombinant Human Interferon Alfa 2a Fusion Protein in Escherichia coli BL21 (DE3) - Santoso, Adi; Kusumawati, Arizah (Annales Bogorienses, 2015)
The rhIFN α2a is expressed as a fusion protein containing thioredoxine and polyhistidine sites at its N terminal. Our previous research has obtained recombinant human IFN α2a (rhIFN α2a) protein that expressed predominantly as a soluble form in E. coli BL21 (DE3). Through systematic approach of various culture conditions, the aim of current this research is to acquire the best condition and its stability of recombinant rhIFN α2a fusion protein in a culture under study. Expression optimization performed by using three parameters, i.e.: temperature, induction time and inducer concentration. Various IPTG concentrations are 0.25, 0.5, 0.75, and 1.0 mM. The incubation time of bacterial cell culture carried out in 3, 4, and 5 hours at temperature 28, 30, and 37°C. The best condition was used to analyze the stability of rhIFN α2a protein expression up to ten generation. The expressed protein was analyzed using SDS PAGE and CBB staining. The optimal culture condition was found to be 37 °C temperature with 4 hours time of induction and 1 mM IPTG concentration. Stability analysis revealed that the rhFN α2a protein expression remained stable until the tenth generation with molecular weight, approximately, 36 kDa.